Homeostasis and Well Being - DOWLING, Malcolm (Institutional Knowledge at Singapore Management University, 2006)
The paper suggests that maintenance of a homeostatic equilibrium provides a rationale for many actions of economic agents. Homeostatic equilibrium has physical, economic, emotional, psychological and environmental dimensions. The characteristics of this equilibrium include feelings of safety, trust, connectedness with friends, family and community, and a predictable and welcoming social and work environment. Individuals generally make decisions that help them move toward and achieve this state of equilibrium. Departure from homeostasis reduces well being and stimulates agents to take actions that will return them to a state of homeostasis. This hypothesis is tested with probit analysis using sample responses from the four waves of the World Values Surveys conducted between 1980 and 2002. Results generally support the homeostasis hypothesis. Variables that reflect departure from homeostasis such as divorce and poor health are highly significant, pointing to a reduction in well being. Variables that reflect the importance of friends, family, a trusting social and work environment have significant impacts to raise well being.